Design and Implementation of Pd based Controller for Accurate Tracking/Heading Angle - Kumar D, Anil; Hariprasad S A, Dr. (International Journal of Engineering and Technology, 2018)
The undesirable effects of the sea on the marine vessel became more noticeable when significant changes were introduced to the design and development of the ship. In order to accurately determine the heading angle of the ship various controllers like PD, pi,pid, predictive and adaptive controllers can be used. Predictive controllers provide accurate heading angles but the computation time becomes a huge challenge. PI controller promises stability but the steady state response time is more. In this work, we have made an attempt to evaluate PD, pi, and PID controller operation for a ship model and it has been inferred that PD is most suitable among the variants for producing the heading angle.
Keywords: .